2023
DOI: 10.3389/fonc.2023.1163463
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and conservative therapy outcomes of anastomotic leakage after gastrectomy: Experience of 3,926 patients from a single gastric surgical unit

Abstract: BackgroundAnastomotic leakage (AL) after gastrectomy is one of the severest postoperative complications and is related to increasing mortality. In addition, no consensus guidelines about strategies of AL treatment have been established. This large cohort study aimed to inspect the risk factors and efficacy of the conservative treatment for AL in patients with gastric cancer.MethodsWe reviewed the clinicopathological data of 3,926 gastric cancer patients undergoing gastrectomy between 2014 and 2021. Results con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
(57 reference statements)
0
2
0
Order By: Relevance
“…Univariate analyses indicated that in the elderly, the low concentrations of plasma hemoglobin, albumin, and cholesterol, diabetes, tumors located in the upper third stomach, the laparoscopic approach, proximal or total gastrectomy, esophagojejunostomy, and long operation time were hte indipendent risk facots facilitating AL development. Multivariate analysis revealed that albumin concentration, diabetes, the laparoscopic approach, and proximal or total gastrectomy were the independent risk factors facilitating AL development (He et al 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Univariate analyses indicated that in the elderly, the low concentrations of plasma hemoglobin, albumin, and cholesterol, diabetes, tumors located in the upper third stomach, the laparoscopic approach, proximal or total gastrectomy, esophagojejunostomy, and long operation time were hte indipendent risk facots facilitating AL development. Multivariate analysis revealed that albumin concentration, diabetes, the laparoscopic approach, and proximal or total gastrectomy were the independent risk factors facilitating AL development (He et al 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…• Site of anastomosis: esophagojejunostomy was the most frequent AL site (73.8%, 59 from 80 patients) with 2.5% mortality and no influence on 5-year survival [26]. The Rouxen-Y and Billroth-I anastomosis had an AL incidence of 0.6% and 1.4%, respectively [27].…”
Section: Risk Factorsmentioning
confidence: 99%